Towards Enhanced Guiding Mechanisms in VR Training through Process Mining - Yigitbas, Enes; Krois, Sebastian; Gottschalk, Sebastian; Engels, Gregor (Proceedings of the 7th International Conference on Human Computer Interaction Theory and Applications (HUCAPP'23))

Cortical thickness and neurocognitive performance in former high‐level female soccer and non‐contact sport athletes - Haase, Franziska Katharina; Prien, Annika; Douw, Linda; Feddermann‐Demont, Nina; Junge, Astrid; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Tailored Frequency Conversion Makes Infrared Light Visible for Streak Cameras - Lüders, Carolin; Gil-Lopez, Jano; Allgaier, Markus; Brecht, Benjamin; Aßmann, Marc; Silberhorn, Christine; Bayer, Manfred (Physical Review Applied)
Keywords: General Physics and Astronomy

A Unifying Approach to Efficient (Near-)Gathering of Disoriented Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Proceedings of the 26th International Conference on Principles of Distributed Systems (OPODIS))

Learning a model is paramount for sample efficiency in reinforcement learning control of PDEs - Werner, Stefan; Peitz, Sebastian (arXiv:2302.07160)
The goal of this paper is to make a strong point for the usage of dynamical models when using reinforcement learning (RL) for feedback control of dynamical systems governed by partial differential equations (PDEs). To breach the gap between the immense promises we see in RL and the applicability in complex engineering systems, the main challenges are the massive requirements in terms of the training data, as well as the lack of performance guarantees. We present a solution for the first issue using a data-driven surrogate model in the form of a convolutional LSTM with actuation. We demonstrate that learning an actuated model in parallel to training the RL agent significantly reduces the total amount of required data sampled from the real system. Furthermore, we show that iteratively updating the model is of major importance to avoid biases in the RL training. Detailed ablation studies reveal the most important ingredients of the modeling process. We use the chaotic Kuramoto-Sivashinsky equation do demonstarte our findings.

Improving students’ attitudes towards peers with special needs: Results from an intervention study. Symposium "Chances and challenges in diverse classrooms" (Sepideh Hassani & Marwin Felix Loeper). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Prerequisites for primary school teachers’ practices in the inclusive classroom. Symposium "Applying the Theory of Planned Behavior in Inclusive Education« (Olli-Pekka Malinen). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Von Herzen! 200 Jahre Missa Solemnis - Schroeter-Wittke, Harald (Praktische Theologie)

A $C^k$-seeley-extension-theorem for Bastiani’s differential calculus - Hanusch, Maximilian (Canadian Journal of Mathematics)
Keywords: extension of differentiable maps

Development of a numerical simulation model for self-piercing riveting of additive manufactured AlSi10Mg - Heyser, Per; Petker, Rudolf; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Laser additive manufacturing processes are used for the production of highly complex geometric structures due to their high geometric freedom. Additive manufacturing processes, in particular powder-based selective laser melting, are used to produce metallic additive manufactured components for the automotive and aerospace industries. Different materials are often joined together to realize sustainable lightweight construction. The production of such mixed construction joints is often realized using mechanical joining technology (e.g. self-piercing riveting). However, there is currently very little experience with the mechanical joining of metallic additive manufacturing components. Furthermore, there is insufficient knowledge about the effects that occur during the mechanical joining of additive manufacturing components. In this article, a method is presented to investigate the joinability of additively manufactured components with conventionally manufactured components using a numerical simulation of the self-piercing riveting process. For this purpose, the additive manufacturing materials are characterized experimentally, the simulation model is configured, and the joining process with additive manufacturing materials is represented in the numerical simulation. Furthermore, the influence of the building direction on the mechanical properties is shown using miniature tensile specimens. Besides the configuration of the simulation model, the influence of heat treatment on the self-piercing riveting process is presented.
Keywords: Mechanical Engineering; General Materials Science

Quantum space, ground space traversal, and how to embed multi-prover interactive proofs into unentanglement - Gharibian, Sevag; Rudolph, Dorian (14th Innovations in Theoretical Computer Science (ITCS))
Savitch's theorem states that NPSPACE computations can be simulated in PSPACE. We initiate the study of a quantum analogue of NPSPACE, denoted Streaming-QCMASPACE (SQCMASPACE), where an exponentially long classical proof is streamed to a poly-space quantum verifier. Besides two main results, we also show that a quantum analogue of Savitch's theorem is unlikely to hold, as SQCMASPACE=NEXP. For completeness, we introduce Streaming-QMASPACE (SQMASPACE) with an exponentially long streamed quantum proof, and show SQMASPACE=QMA_EXP (quantum analogue of NEXP). Our first main result shows, in contrast to the classical setting, the solution space of a quantum constraint satisfaction problem (i.e. a local Hamiltonian) is always connected when exponentially long proofs are permitted. For this, we show how to simulate any Lipschitz continuous path on the unit hypersphere via a sequence of local unitary gates, at the expense of blowing up the circuit size. This shows quantum error-correcting codes can be unable to detect one codeword erroneously evolving to another if the evolution happens sufficiently slowly, and answers an open question of [Gharibian, Sikora, ICALP 2015] regarding the Ground State Connectivity problem. Our second main result is that any SQCMASPACE computation can be embedded into "unentanglement", i.e. into a quantum constraint satisfaction problem with unentangled provers. Formally, we show how to embed SQCMASPACE into the Sparse Separable Hamiltonian problem of [Chailloux, Sattath, CCC 2012] (QMA(2)-complete for 1/poly promise gap), at the expense of scaling the promise gap with the streamed proof size. As a corollary, we obtain the first systematic construction for obtaining QMA(2)-type upper bounds on arbitrary multi-prover interactive proof systems, where the QMA(2) promise gap scales exponentially with the number of bits of communication in the interactive proof.

Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Konzeptentwicklung für ein Stahlbatteriegehäuse unter besonderer Berücksichtigung der Fügetechnik und des Korrosionsschutzes - Schmolke, Tobias; Meschut, Gerson; Spohr, Sebastian; Eckstein, Lutz; Brunner-Schwer, Christian; Rethmeier, Michael; Nothhelfer-Richter, Rolf; Hilt, Michael

Leak Tightness of Bonded Joints in Battery Housings Under Mechanical and Corrosive Loads - Schmolke, Tobias; Meschut, Gerson

Interaktive Einkaufserlebnisse in Innenstädten

Projekt FLEMING – Predictive Maintenance von zentralen Komponenten des Mittelspannungsnetzes - zur Heiden, Philipp (DASC-PM v1.1 Fallstudien)

Frauensache(n)? Mode und Gender aus feministischer Perspektive. - Haller, Melanie (Tietze, Katharina/Schnittler, Anna-Brigitta: Mode und Gender.)

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Nagel, Christof; Carillo Beber, Vinicius; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimental investigation of the fatigue behavior and calculation of the service life of adhesively bonded joints - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

Experimental and numerical investigation of the damping properties of adhesively bonded tubular steel joints - Göddecke, Johannes; Meschut, Gerson; Damm, Jannis; Albiez, Matthias; Ummenhofer, Thomas; Kötz, Fabian; Matzenmiller, Anton (The Journal of Adhesion)